Eight weeks of Paritaprevir/r/Ombitasvir + Dasabuvir in HCV genotype 1b with mild‐moderate fibrosis: Results from a real‐world cohort. (12th November 2018) - Puigvehí, Marc; De Cuenca, Beatriz; Viu, Ana; Diago, Moisés; Turnes, Juan; Gea, Francisco; Pascasio, Juan M.; Lens, Sabela; Cabezas, Joaquín; Badia, Ester; Olveira, Antonio; Morillas, Rosa M.; et al.
Abstract: Background & Aims: The interferon‐free regimen paritaprevir/ritonavir, ombitasvir + dasabuvir (PTV/r/OBV/DSV) has shown high efficacy in patients with hepatitis C virus (HCV) genotype 1b infection when administered for 8 or 12 weeks, but data regarding the 8‐week treatment are scarce. The aim of our study was to assess the efficacy and safety of the 8‐week administration of PTV/r/OBV/DSV in a real‐world cohort. Methods: We performed a multicentre observational study from Spanish Hepa‐C database including patients receiving 8 weeks of PTV/r/OBV/DSV (October 2016‐November 2017). Those with advanced fibrosis, with non‐genotype 1b or who were treatment‐experienced were excluded. Results: A total of 211 patients were registered from 23 Spanish centres; eleven were excluded. At baseline, 42.5% (n = 85) were male, median (range) age was 57 (23‐86), ALT was 45 (11‐494) IU/mL, viral load was 6.1 (3.3‐8.2) log10 IU/mL, and 74.5% had mild liver fibrosis (F0‐F1) and 25.5% moderate fibrosis (F2). At the end of treatment (EOT), HCV viral load was undetectable in 100% (200/200). Seven patients relapsed after treatment discontinuation. Sustained virological response (SVR12) rates by intention‐to‐treat analysis were 96% (192/200). Regarding treatment safety, 2 patients developed ALT elevation >5x ULN, but there were no treatment discontinuations. One patient died 7 weeks after EOT. Conclusion: Treatment with PTV/r/OBV/DSV in genotype 1b‐infected treatment‐naive patients with mild‐moderate fibrosis shows excellent efficacy and safety in real life, similarly to clinical trials. Clinicaltrials.gov, number: NCT03122132.